Digital transformation capabilities moderate the effects of entrepreneurial resources on MSMEs performance: A multigroup analysis in Makassar city, Indonesia - Syulhasbiullah, Muh; Radianto, Wirawan Endro Dwi; Tambunan, Damelina Basauli (Edelweiss Applied Science and Technology, 2026)
Digital transformation is reshaping MSMEs’ value-creation logics and shifting coordination toward platform ecosystems, yet it remains unclear when Digital Transformation Capabilities (DTC) strengthen entrepreneurial resources into performance. Accordingly, this study tests DTC as a boundary condition moderating the effects of Entrepreneurial Network (EN), Entrepreneurial Orientation (EO), and Entrepreneurial Competence (EC) on MSMEs’ performance (SMEP) among MSMEs in Makassar, Indonesia. Survey data from 254 MSME owners and managers were analyzed using PLS-SEM, with MICOM-based measurement invariance assessment and multigroup analysis by business age. The results show that EN, EO, and EC contribute positively to SMEP and remain stable across both age groups. DTC does not moderate the EO–performance or EC–performance relationships. In contrast, the EN×DTC interaction is negative in the overall sample and is significant in enterprises older than 3 years, while it is not detected in enterprises aged 0–3 years. These findings imply that DTC functions as a selective conversion capability that can introduce network-coordination frictions at certain maturity stages; therefore, digital strategy should prioritize relationship orchestration rather than network expansion alone. The study’s originality lies in integrating bundled entrepreneurial resources with DTC and conducting invariance-supported cross-group comparisons in the context of MSMEs in Makassar, Indonesia.